Ethnoecological investigation of medicinal plants in Andracha District, Southwest Ethiopia - Tessema, Zewdie Kassa; Melese, Daniel; Haile, Belay; Awoke, Ashebir; Asnakew, Mulye (Ethnobotany Research and Applications, 2025)
Background: Ethiopian traditional medicine has been a key aspect of the primary healthcare system for a prolonged period. The current study documented medicinal plants and associated knowledge with threats in the Andracha District of Southwest Ethiopia. It explored the link between informants’ knowledge and their demographics. Methods: The study was conducted from November 2020 to April 2022 where 128 respondents (88 regular and 40 healers) participated. Data was collected using semi-structured interviews, focus group discussions, market surveys, and field observations. Authenticated voucher specimens were deposited in the herbarium. Data analysis was through ethnobotanical indices complemented with statistical tests, models, and ordination methods in R software. Results: A total of 100 medicinal plants in 88 genera with 47 families were identified. Asteraceae and Lamiaceae are the most frequent. Herbs were the most dominant. Leaves followed by roots were the most utilized plant parts. Fresh preparations were the most preferred, with oral administration being the most common, followed by topical use. Firewood, invasive alien species, and charcoal were the most threatening factors. Significant associations among informants’ knowledge and their demographics were observed. Conclusion: Traditional ethnomedicinal plant knowledge documented in Anderacha district significantly adds to the current ethnomedicinal plant knowledge of Ethiopia. In situ conservation priorities are needed to minimize the ever-declining number of medicinal plants, endemic species such as Echinops kebericho, Erythrina brucei, Milletia ferruginea, as well as associated indigenous knowledge due to threatening factors. Key words: Biodiversity, Biosphere reserve, Culture, Ethnobotany, Ethnomedicine, Herbalists.